Position Displacement of Diffuse Interstellar Bands*: Position Displacement of Diffuse Interstellar Bands. (4th January 2016) - Galazutdinov, G.; Krełowski, J.; Beletsky, Y.; Valyavin, G.
Abstract: We reconsider the already published phenomenon of the blue shift of diffuse interstellar bands, observed in spectra of HD34078 (AE Aur) and members of the Sco OB1 association, in particular HD152233. We have analyzed 29 diffuse bands. Some of them, already proven as blue-shifted in our earlier study, are now confirmed using another instrument: the 6.5 m Clay telescope equipped with the MIKE spectrograph. The high signal-to-noise ratio (over 600) of our spectra allowed us to reveal even small small-scale displacements of positions (both blue and redshifts) of diffuse bands along the considered lines of sight. In some cases, the magnitude of deviation exceeds 10 km s -1 . Also, we prove that profiles of many diffuse bands in spectra of HD34078 suffer significant broadening. The origin of the observed phenomena is discussed.